Arabic Language Learning Strategies and Suporting Factors At MAN 1 Surakarta, Central Java Indonesia - Solihin, Muhammad; Khomsin, Khomsin; Rafik, Abdul (International Journal of Science and Environment (IJSE), 2026)
This research explains Arabic learning strategies and the factors that support them (case study at MAN 1 Surakarta Central Java Indonesia).Learning strategies are crucial for students in learning Arabic because they help students accelerate in mastering vocabulary and composing Arabic sentences properly and correctly. Known that most Arabic language learning in schools experiences many difficulties in the process because they have not been able to use appropriate and appropriate strategies. Therefore, in overcoming this problem, the learning process requires various strategies to maximize the learning process and results. The action of using motivational strategies, vocabulary grouping strategies, vocabulary memorization strategies, and others will increase students' Arabic language skills. Similarly, supporting factors such as the presence of Middle Eastern alumni teachers and graduates of special program schools (MAN PK), the formation of a language environment through dormitories and others are very important for the success of the Arabic language learning process because in it there are a series of important steps and procedures that can help students find effective and enjoyable Arabic language learning actions.